Global Scale Transcriptional Profiling of Two Contrasting Barley Genotypes Exposed to Moderate Drought Conditions: Contribution of Leaves and Crowns to Water Shortage Coping Strategies - Svoboda, Pavel; Janská, Anna; Spiwok, Vojtěch; Prášil, Ilja T.; Kosová, Klára; Vítámvás, Pavel; Ovesná, Jaroslava (Frontiers in Plant Science, 2016)
Drought is a serious threat for suistanable argiculture. Barley represents a species well adapted to envrinonmental stresses including drought. To elucidate the adaptive mechanism of barley on transcriptional level we evaluated transcriptomic changes of two contrasting barley cultivars upon drought using the microarray technique on the level of leaves and crowns. Using bioinformatic tools, differentially expressed genes in treated vs. non-treated plants were identified. Both genotypes revealed tissue dehydration under drought conditions as shown at water saturation deficit and osmotic potential data; however, dehydration was more severe in Amulet than in drought-resistant Tadmor under the same ambient conditions. Performed analysis showed that Amulet enhanced expression of genes related to active plant growth and development, while Tadmor regarding the stimulated genes revealed conservative, water saving strategy. Common reactions of both genotypes and tissues included an induction of genes encoding several stress-responsive signalling proteins, transcription factors as well as effector genes encoding proteins directly involved in stress acclimation. In leaf, tolerant cultivar effectively stimulated mainly the expression of genes encoding proteins and enzymes involved in protein folding, sulfur metabolism, ROS detoxification or lipid biosynthesis and transport. The crown specific reaction of tolerant cultivar was an enhanced expression of genes encoding proteins and enzymes involved in cell wall lignification, ABRE-dependent ABA signaling, nucleosome remodelling, along with genes for numerous jasmonate induced proteins.